2018
DOI: 10.1097/sla.0000000000002731
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Laparoscopic Common Bile Duct Exploration Combined with Cholecystectomy for the Management of Cholecysto-choledocholithiasis

Abstract: The updated meta-analysis first confirms that LCBDE+LC is superior to pre-EST+LC both in perioperative safety and short- and long-term postoperative efficacy, which should be considered as optimal treatment choice for cholecysto-choledocholithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 37 publications
1
84
1
8
Order By: Relevance
“…Due to the potential seriousness of biliary complications, it begs the question of the current global approach to intra-operative cholangiography and single stage bile duct clearance. A recent meta-analysis by Pan et al [84] found performance of intra-operative cholangiography to have superior outcomes in managing cholecystocholedocholithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential seriousness of biliary complications, it begs the question of the current global approach to intra-operative cholangiography and single stage bile duct clearance. A recent meta-analysis by Pan et al [84] found performance of intra-operative cholangiography to have superior outcomes in managing cholecystocholedocholithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis showed that LCBDE had a higher stones clearance rate, lower retained stone rate and lithiasis recurrence rate and lower hospital stays and less total charges than the ERCP procedure. Thus, the LCBDE should be considered the optimal treatment choice for the patient with cholecysto‐choledocholithiasis …”
Section: Discussionmentioning
confidence: 99%
“…The treatment of CBDS largely varies. It is still controversial whether there is any treatment superior to the others . Laparoscopic surgery or ERCP alone may not achieve the best therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is still controversial whether there is any treatment superior to the others. [4][5][6] Laparoscopic surgery or ERCP alone may not achieve the best therapeutic effect. A reasonable combination of laparoscopy, choledochoscopy and duodenoscopy could maximize the benefit.…”
Section: Discussionmentioning
confidence: 99%